FORMULATION AND EVALUATION OF SOLID DISPERSION INCORPORATED FAST DISINTEGRATING TABLETS OF TENOXICAM USING DESIGN OF EXPERIMENT (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The aim of the present work is to develop fast dissolving tablets from the solid dispersion of Tenoxicam for enhancement of solubility. The solid dispersions of Tenoxicam were prepared with Kollidon CL, PVP K30 and Poloxamer 127, in 1:1:1, 1:2:1 and 1:3:1 by using solvent evaporation method. The prepared solid dispersions were analyzed for all the physical parameters, drug: carrier interactions like FTIR, SEM, XRD. Solid dispersions showed a better dissolution compared to the pure drugs and among all the other formulations SD9 shows high percentage drug release i.e. 99.11 ± 5.17% for 90 min and selected as an optimized formulation for the preparation of fast disintegrating tablets of Tenoxicam. Gellan Gum, Fenugreek Seed Mucilage and L-HPC (low, middle and high concentrations) used in the preparation of fast disintegrating tablets prepared by direct compression method using 33 Response surface method. The post compression parameters of all the prepared tablets were within the limits. TF13 was selected as optimized formulation based on its highest disintegration time 36 sec and drug release 99.68 ± 1.52% for 10 min. Drug-excipients characterization also revealed that there is no interaction. Hence it concluded that solid dispersions incorporated fast disintegrating tablets is very useful approach for immediate release of Tenoxicam in the efficient management of inflammation and pain.